Odontochilus putaoensis (Orchidaceae), a new record and key to the genus for China - Sun , M.; Jin , Y.; Kumar , P.; Tian, H.Z. (Rheedea, 2026)
Odontochilus putaoensis X.H.Jin, L.A.Ye & A.T.Mu, a jewel orchid hitherto known only from Myanmar and Laos, is recorded from China for the first time. A detailed morphological description and a colour figure are provided, together with information on habitat, distribution and tentative conservation status. An updated identification key to the genus Odontochilus in China is also provided.